1998
DOI: 10.1002/(sici)1097-0134(19980215)30:3<264::aid-prot6>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the active site of factor Xa by selective inhibitors: An NMR and MD study

Abstract: The structure of two selective inhibitors, Ac-Tyr-Ile-Arg-Ile-Pro-NH2 and Ac-(4-Amino-Phe)-(Cyclohexyl-Gly)-Arg-NH2, in the active site of the blood clotting enzyme factor Xa was determined by using transferred nuclear Overhauser effect nuclear magnetic resonance (NMR) spectroscopy. They represent a family of peptidic inhibitors obtained by the screening of a vast combinatorial library. Each structure was first calculated by using standard computational procedures (distance geometry, simulated annealing, energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…18 It was also shown that missing or badly placed water molecules in fXa may lead to computational artifacts. [19][20][21][22][23] fXa is one of the key enzymes in the blood coagulation cascade. [24][25][26][27][28][29][30][31][32][33][34][35] It is the joining point for the extrinsic and the intrinsic pathway of fibrin production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 It was also shown that missing or badly placed water molecules in fXa may lead to computational artifacts. [19][20][21][22][23] fXa is one of the key enzymes in the blood coagulation cascade. [24][25][26][27][28][29][30][31][32][33][34][35] It is the joining point for the extrinsic and the intrinsic pathway of fibrin production.…”
Section: Introductionmentioning
confidence: 99%
“…In all experimental X-ray structures with resolved water molecules, it is filled with a chain of water molecules that are considered to be important for the catalytic function. If some of these waters are not seen in a serine protease X-ray structure, this is probably due to low resolution of the experiment . It was also shown that missing or badly placed water molecules in fXa may lead to computational artifacts. …”
Section: Introductionmentioning
confidence: 99%
“…TxR was positioned considering channels found with Molcad Multi‐channel, directing the fluorophore part towards the extra cellular surface, as it is charged. A local minimisation was then undertaken as described above in the Tripos force field (Fraternali et al. 1998).…”
Section: Methodsmentioning
confidence: 99%
“…All the minimisation procedure was undertaken without charge and in Amber 4.1 force field (Fraternali et al. 1998) with a maximum of 25 simplex steps coupled to a Powell (Fraternali et al. 1998) method, with an energy termination gradient of 0.05 × kcal × mol −1 × Å −1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation